MODELLING OF THE SALINITY PENETRATION AT CAI RIVER IN NHA TRANG IN THE DRY SEAS ON USING 1D AND 2D MODELS - Duong, Pham Xuan (Vietnam Journal of Marine Science and Technology, 2008)
The results on modelling of the penetration of sea water at Cai River in Nha Trang in dry season using one and two dimensions models are shown in this paper. Th e calculated results were compared with the measured data. It is shown that the modelled results are suitable in quality and quantity with the measured ones. It shows that the models and algorithms can be used for calculation and forecasting of the salinity penetration at Cai River in Nha Trang.